2023
DOI: 10.12669/pjms.39.2.7103
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of precise and quantitative rapid pulmonary rehabilitation nursing program for elderly patients with lung cancer during the perioperative period: A randomized controlled trial

Abstract: Objective: Preoperative rehabilitation should improve the functional condition of patients. Improvements in metabolism, lung mechanics, cardiovascular function, and muscle-function can be achieved by pulmonary rehabilitation. Hence, we focused on elderly patients with lung cancer undergoing surgery, and assessed the effectiveness of a rapid and precise pulmonary rehabilitation nursing program during the perioperative period. Methods: This randomized controlled trial at the department of thoracic surgery;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Finally, implementing the program may improve overall physical fitness of the patient, which can help to reduce the risk of complications after the surgery 34 and shorten the time to discharge. 35 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, implementing the program may improve overall physical fitness of the patient, which can help to reduce the risk of complications after the surgery 34 and shorten the time to discharge. 35 …”
Section: Discussionmentioning
confidence: 99%
“…Finally, implementing the program may improve overall physical fitness of the patient, which can help to reduce the risk of complications after the surgery 34 and shorten the time to discharge. 35 Nurses played a primary role in providing rehabilitation intervention across almost all the included studies. Nurses were either in a full-time role exclusively for the provision of pulmonary rehabilitation intervention or provided rehabilitation in addition to their other responsibilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients are gradually required to achieve their target volumes with the guidance of this device. In a study [20] , elderly lung cancer patients were provided with a respiratory trainer to assist them in respiratory training and to monitor their progress after surgery. The results indicated that the test group, which used the respiratory trainer, exhibited better lung function, shorter length of stay, and improved quality of life compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…As indicated in the included studies (Table 1), routine The use of RRN has been steadily increasing, fueled by the growing body of evidence suggesting its potential benefits in postoperative care (Liang et al, 2021). Some studies have reported positive outcomes associated with RRN, such as reduced postoperative pain, improved physical function, shortened hospital stays, and a lower incidence of complications (Chang et al, 2022;Chen et al, 2023;Feng et al, 2022;Ji & Yan, 2023). In addition, RRN has been shown to enhance patient satisfaction with nursing care and contribute to better resource utilization in healthcare settings (Ross et al, 2011).…”
Section: Introductionmentioning
confidence: 99%